Interpretasi Makna Walad dan Implikasinya terhadap Hukum Kewarisan Anak Perempuan dalam Perspektif Putusan Pengadilan Agama - Fitri, Al (Legalita, 2025)
This study examines the interpretation of the meaning of walad and its implications for the inheritance status of girls from the perspective of Religious Court decisions. The term walad in the Qur'an and Islamic jurisprudence is often understood generally as 'child', but there are differences in interpretation among scholars regarding the scope of its meaning, whether it includes only boys or also girls. This difference in understanding has implications for the distribution of inheritance rights, particularly in the context of equality between boys and girls. This study uses a qualitative approach with normative legal research methods through a study of tafsir literature, classical fiqh books, and an analysis of several relevant Religious Court decisions. The results show that some Religious Court decisions interpret walad inclusively, namely to include both boys and girls, in line with the principles of justice and protection of rights in contemporary Islamic law. The implication of this interpretation is the strengthening of the legal position of girls as legitimate heirs and entitled to receive a share in accordance with the provisions of the Qur'an. This study emphasizes the importance of contextualizing the meaning of walad in religious court practice to align with the values ​​of gender justice and the development of modern Islamic law.